Enhancing Junior High School Students' Digital Advertisement Writing through Book Creator: A Quasi-Experimental Study - Eka Malinda Rahmawati; Khaerudin Kurniawan; Isah Cahyani (AL-ISHLAH: Jurnal Pendidikan, 2025)
Developing students' ability to write effective digital advertisement texts is crucial in today's media-rich environment. This study explores the impact of the Book Creator application on enhancing junior high school students’ digital advertisement writing skills. A quasi-experimental design with a pretest-posttest control group was employed. The participants included 60 eighth-grade students who were randomly assigned to either the experimental group, which received instruction using the Book Creator app, or the control group, which followed traditional teaching methods. A validated writing skills test was used to measure students’ performance before and after the intervention. Data were analyzed using tests of normality, homogeneity, paired t-tests, and independent t-tests. Findings revealed a significant improvement in the post-test scores of the experimental group (M = 87.70) compared to the control group (M = 75.27), with a mean difference of 12.43 (t = 7.268, p 0.001). The experimental group demonstrated enhanced ability in constructing persuasive, well-structured, and visually supported digital advertisements. The results suggest that integrating Book Creator into writing instruction supports the development of digital writing competencies, including creativity, structure, and multimedia integration. The study highlights the potential of digital tools to foster digital literacy and engagement among junior high school learners.